Mammal extinctions and the increasing isolation of humans on the tree of life - Pavoine, S; Bonsall, M; Davies, J; Masi, S (Wiley, 2019)
A sixth great mass extinction is ongoing due to the direct and indirect effects of human pressures. However, not all lineages are affected equally. From an anthropocentric perspective, it is often purported that humans hold a unique place on Earth. Here, we show that our current impacts on the natural world risk realizing that expectation. We simulated species loss on the mammalian phylogenetic tree, informed by species current extinction risks. We explored how Homo sapiens could become isolated in the tree if species currently threatened with extinction disappeared. We analyzed correlates of mammal extinctions risks that may drive this isolation pattern. We show that, within mammals, and more particularly within primates, extinction risks increase with the number of known threat types, and decrease with geographic range size. Extinctions increase with species body mass, trophic level, and the median longitudinal extent of each species range in mammals but not within primates. The risks of extinction are frequently high among H. sapiens close relatives. Pruning threatened primates, including apes (Hominidae, Hylobatidae), from the tree of life will lead to our species being among those with the fewest close relatives. If no action is taken, we will thus not only lose crucial biodiversity for the preservation of Earth ecosystems, but also a key living reference to what makes us human.